(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes the analysis of the concept of motive, the educational significance of theoretical information about motive collected in Psychological Science, the importance of the fact that any activity psychologically arises under the influence of certain motives, educational motives are formed for mastering, mastering and learning in the educational process.